2013
DOI: 10.1002/ppap.201300067
|View full text |Cite
|
Sign up to set email alerts
|

Etching of Blood Proteins in the Early and Late Flowing Afterglow of Oxygen Plasma

Abstract: Films of proteins fibrinogen and albumin are exposed to neutral reactive particles in order to study their etching rates in early and late oxygen afterglows of microwave plasma. The etching rates are determined at different pressures between 50 and 400 Pa. The etching rates for both proteins first increase with the increasing pressure, while later they reach a constant value. Furthermore, the etching rates are higher in the early than in the late afterglow. The concentration of all available species in the aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…However, due to lack of data at this stage, no other reactions in the overall chemical pathway can be proposed. Recent works on proteins by Vesel et al showed a synergetic effect of O and O 2 (a), i.e., a pathway that could match with the present inferred scheme where the singlet state of oxygen is proposed to help open the ring once a radical is formed from hydrogen abstraction by atomic oxygen. According to these authors, O 3 does not play a significant role in afterglow.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…However, due to lack of data at this stage, no other reactions in the overall chemical pathway can be proposed. Recent works on proteins by Vesel et al showed a synergetic effect of O and O 2 (a), i.e., a pathway that could match with the present inferred scheme where the singlet state of oxygen is proposed to help open the ring once a radical is formed from hydrogen abstraction by atomic oxygen. According to these authors, O 3 does not play a significant role in afterglow.…”
Section: Resultssupporting
confidence: 82%
“…Mozetič showed how to control oxidation of some organic compounds in oxygen plasma . The same group investigated in 2014 the interaction of early and late afterglows with blood proteins, revealing a synergetic effect of O and O 2 (a) species involved the etching process. We showed how O atoms and O 2 molecules interact with CC and CH bonds by understanding the oxidation mechanisms at low temperature (i.e., below the melting point of the studied materials) of hexatriacontane (C 36 H 74 ), a long chain alkane .…”
Section: Introductionmentioning
confidence: 99%
“…A good candidate can be O 2 (a) molecules, but unfortunately, there exists no technique for determination of their concentration. As shown in our recent paper, etching is actually due to synergistic effect between O‐atoms and O 2 (a) molecules . The etching rate is increasing with the increasing pressure (see also Fig.…”
Section: Resultssupporting
confidence: 63%
“…In such conditions the pressure in the treatment chamber was 50 Pa. In case the working gas was oxygen, the concentration of neutral oxygen atoms in the ground state at the position next to the sample was approximately 7 × 10 20 m −3 [19], whereas, in the case of nitrogen, the dissociation fraction was somehow lower and the N-atom density was only approximately 4 × 10 20 m −3 . The treatment time for both cases was 30 s.…”
Section: Methodsmentioning
confidence: 99%